Mismatched perfusion defects on routine ventilation‐perfusion scans after lung transplantation. Issue 6 (20th March 2022) - Li, David; Abele, Jonathan; Sunner, Parveen; Varughese, Rhea; Hirji, Alim; Weinkauf, Justin; Nagendran, Jayan; Lien, Dale; Halloran, Kieran
Abstract: Background: Incidental pulmonary embolism (PE) is a challenging entity with unclear treatment implications. Our program performs routine ventilation‐perfusion (VQ) scans at 3‐months post‐transplant to establish airway and vascular function. We sought to determine the prevalence and prognostic implications of mismatched perfusion defects (MMPD) found on these studies, hypothesizing they would be associated with a benign prognosis. Methods: We studied VQ scans obtained routinely at 3‐months post‐transplant from double lung transplant recipients 2005–2016 for studies with MMPD interpreted as high or intermediate probability for PE. We tested the relationship between MMPD and 1‐year survival via chi square testing, overall survival via Kaplan Meier analysis with log rank testing and peak forced expiratory volume in 1 second (FEV1) percent predicted via t‐testing. Results: Three hundred and seventy‐three patients met inclusion criteria, of whom 35 (9%) had VQ scans with MMPDs interpreted by radiologists as high or intermediate probability for PE. Baseline recipient and donor characteristics were similar between groups. Seven patients (20%) in the MMPD group were treated with therapeutic anticoagulation. Patients with MMPD had similar 1‐year survival (100% vs. 98%, P  = 1.00), overall survival (log rank P  = .90) and peak FEV1% predicted (94% [SD 20%] vs. 92% [SD 21%]; P  = .58). Anticoagulation did not affect these relationships. Conclusion: Mismatched perfusion defects on routine post‐transplant VQ scan were not associated with a difference in survival or lung function. A conservative approach to these changes may be a viable option in the absence of other anticoagulation indications.